A study on the impact of systematic desensitization training on competitive anxiety among Latin dance athletes - Chen, Jie; Zhou, Duoqi; Gong, Dan; Wu, Shunli; Chen, Weikai (Frontiers in Psychology, 2024)
Objective In the domain of competitive events, Latin dance athletes have always suffered competitive anxiety, which is a prevalent and prevailing psychological facet, in pre-, intra-, and post-competitive engagements. Usually, the implementation of systematic desensitization training is an efficacious approach to reduce competitive anxiety levels in routine sports to fortify psychological resilience of athletes (like swimming, volleyball, and basketball). This study focuses on the effect of systematic desensitization training on competition anxiety in the training of Latin dancers to establish good mental ability and promote the competitive ability of athletes. Methodology The “Sports Competition Anxiety Test Questionnaire” was used to evaluate and classify the competitive anxiety levels of 150 Latin dance athletes. Then, the top 48 participants were selected (24 in the intervention cohort and 24 in the non-intervention cohort) as the study participants after stratifying anxiety score levels from the highest to the lowest. The intervention group was treated with an 8-week psychological intervention by employing systematic desensitization training techniques (encompassing imagery desensitization and in vivo desensitization). The anxiety levels of the subjects were quantified by employing the “Sport Competition Trait Anxiety Inventory” (CCTAI-C) and the “Competitive State Anxiety Inventory” (CSAI-2) to scrutinize the efficacy of systematic desensitization training in regulating competitive anxiety levels among Latin dance athletes. Results After applying systematic desensitization training, the intervention group displayed a notable reduction in sport cognitive trait anxiety. Specifically, there was a decrease of 29.37% in social evaluation anxiety, 20.31% in competition preparation anxiety, 16.98% in performance anxiety, 25.16% in failure anxiety, 34.47% in opponent’s ability anxiety, and 25.16% in injury anxiety. Moreover, for competitive state anxiety, cognitive state anxiety and somatic state anxiety decreased by 39.19 and 21.43%. The state self-confidence increased by 14.42%. Conclusion The result indicated that systematic desensitization training not only mitigates anxiety but also positively intervenes in sports-related anxiety. Moreover, systematic desensitization training can significantly diminish competitive anxiety among Latin dance athletes to bolster confidence during competitions. Integrating desensitization training into the regular regimen of Latin dance practice has the potential to fortify dancers’ psychological resilience against anxiety.